2016
DOI: 10.4081/jlimnol.2016.1479
|View full text |Cite
|
Sign up to set email alerts
|

The success of the cyanobacterium Cylindrospermopsis raciborskii in freshwaters is enhanced by the combined effects of light intensity and temperature

Abstract: <p>Toxic cyanobacterial blooms in freshwaters are thought to be a consequence of the combined effects of anthropogenic eutrophication and climate change. It is expected that climate change will affect water mixing regimes that alter the water transparency and ultimately the light environment for phytoplankton. Blooms of the potentially toxic cyanobacterium <em>Cylindrospermopsis raciborskii</em> are expanding from tropical towards temperate regions. Several hypotheses have been proposed to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 60 publications
2
22
0
Order By: Relevance
“…Filamentous cyanobacterial blooms are common in well‐mixed waters with different light intensity conditions (Aguilera et al., ; Havens, James, East, & Smith, ; Paerl et al., ). For instance, while some species such as Cylindrospermopsis raciborskii , a species phylogenetically related to R. mediterranea (Aguilera, Berrendero, Kaštovský, Echenique, & Salerno, in press; Moustaka‐Gouni, Kormas, Vardaka, Katsiapi, & Gkelis, ), succeed under high‐ Z eu / Z mix conditions (values ≥1) (Bonilla et al., ), P. agardhii blooms in highly turbid water columns ( Z eu / Z mix < 1; Bonilla et al., ) (Scheffer et al., ). Variable conditions in the Z eu / Z mix ratio during our study (range 0.37–1.42) may have favoured both cyanobacteria species in combination with changing nutrient conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Filamentous cyanobacterial blooms are common in well‐mixed waters with different light intensity conditions (Aguilera et al., ; Havens, James, East, & Smith, ; Paerl et al., ). For instance, while some species such as Cylindrospermopsis raciborskii , a species phylogenetically related to R. mediterranea (Aguilera, Berrendero, Kaštovský, Echenique, & Salerno, in press; Moustaka‐Gouni, Kormas, Vardaka, Katsiapi, & Gkelis, ), succeed under high‐ Z eu / Z mix conditions (values ≥1) (Bonilla et al., ), P. agardhii blooms in highly turbid water columns ( Z eu / Z mix < 1; Bonilla et al., ) (Scheffer et al., ). Variable conditions in the Z eu / Z mix ratio during our study (range 0.37–1.42) may have favoured both cyanobacteria species in combination with changing nutrient conditions.…”
Section: Discussionmentioning
confidence: 99%
“…For example, its high affinity for phosphorus uptake and strain variation in phosphorus storage [23] has allowed its dominance in habitats with phosphate deficiency [24]. Growth under a broad range of temperature and light conditions is also an important capability for successful invasion [18,[25][26][27]. The dual roles of light and temperature in the dominance of certain species is not fully understood, and field and laboratory studies have shown contrasting results [7,28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Stage‐specific population growth rate ( r ) and somatic growth rate (SGR) were used as measures of fitness. Raphidiopsis raciborskii was used as a food stressor because of its tropical origin (Padisák, ), high thermal and light tolerance (Bonilla et al, ; Recknagel et al, ), high invasiveness, wide (especially in Europe), and still‐expanding distribution (Wilk‐Woźniak et al, ; Kokociński et al, ; Rzymski et al, ).…”
Section: Introductionmentioning
confidence: 99%